Systematic review of brain-eating amoeba: a decade update - Ahmad Zamzuri, Mohd ‘Ammar Ihsan; Abd Majid, Farah Nabila; Mihat, Massitah; Ibrahim, Siti Salwa; Ismail, Muhammad; Abd Aziz, Suriyati; Mohamed, Zuraida; Rejali, Lokman; Yahaya, Hazlina; Abdullah, Zulhizzam; Hassan, Mohd Rohaizat; Dapari, Rahmat; et al. (MDPI, 2023)
Introduction: Primary amoebic meningoencephalitis (PAM) is a rare but lethal infection of the brain caused by a eukaryote called Naegleria fowleri (N. fowleri). The aim of this review is to consolidate the recently published case reports of N. fowleri infection by describing its epidemiology and clinical features with the goal of ultimately disseminating this information to healthcare personnel. Methods: A comprehensive literature search was carried out using PubMed, Web of Science, Scopus, and OVID databases until 31 December 2022 by two independent reviewers. All studies from the year 2013 were extracted, and quality assessments were carried out meticulously prior to their inclusion in the final analysis. Results: A total of 21 studies were selected for qualitative analyses out of the 461 studies extracted. The cases were distributed globally, and 72.7% of the cases succumbed to mortality. The youngest case was an 11-day-old boy, while the eldest was a 75-year-old. Significant exposure to freshwater either from recreational activities or from a habit of irrigating the nostrils preceded onset. The symptoms at early presentation included fever, headache, and vomiting, while late sequalae showed neurological manifestation. An accurate diagnosis remains a challenge, as the symptoms mimic bacterial meningitis. Confirmatory tests include the direct visualisation of the amoeba or the use of the polymerase chain reaction method. Conclusions: N. fowleri infection is rare but leads to PAM. Its occurrence is worldwide with a significant risk of fatality. The suggested probable case definition based on the findings is the acute onset of fever, headache, and vomiting with meningeal symptoms following exposure to freshwater within the previous 14 days. Continuous health promotion and health education activities for the public can help to improve knowledge and awareness prior to engagement in freshwater activities.